Penerapan Metode Belajar Dengan Simulasi Komputer Dapat Meningkatkan Kemampuan Praktek Pola Peserta Didik - Nababan, Lerisma (Komunitas Manajemen Kompetitif, 2017)
Abstract: Practice patterns in science lessons were admittedly relatively difficult to understand and takes a relatively long time, so that student learning outcomes to be low. Through action research methods were implemented in elementary schools with tests and observation and analyzed with descriptive techniques. The results showed that the application of computer simulation educational learning tool to improve science learning outcomes of students in the sixth grade energy in natural science subjects turned out to increase student learning outcomes. Keywords: Computer Simulation Methods, Ability Practice Patterns